BER and PSD Improvement of FBMC with Higher Order QAM Using Hermite Filter for 5G Wireless Communication and beyond. (9th January 2023) - Dumari, Hise Teferi; Gelmecha, Demissie Jobir; Shakya, Rajeev K.; Singh, Ram Sewak
Abstract : Nowadays, multicarrier modulation schemes are being widely used in wireless communication system than single-carrier modulation techniques. Single-carrier modulation schemes are less capable of dealing with multipath fading channels than multicarrier modulation schemes, which results in lower spectral efficiency. Multicarrier modulation schemes have the ability to overcome multipath fading channels. Multicarrier modulation technique currently used in 4G technology in many countries is OFDM and it is easy for implementation, immune to interference, and provide fast data rate. However, the rising users demand on wireless communication resulted in need for further advancement of wireless communication system. The present OFDM transmission does not fulfill the requirements of 5G wireless communication system and beyond due to major limitations such as out of band emission and usage of cyclic prefix. To overcome the challenges of OFDM, different modulation schemes like Filter Bank Multicarrier with Offset-QAM, Filter Bank Multicarrier with QAM, Universal Filter Multicarrier, Filtered-OFDM, and Weighted Overlap and Added-OFDM are proposed. In this study, the Filter Bank Multicarrier with QAM using Hermite prototype filter is proposed to overcome drawbacks of OFDM and all other proposed waveforms. The performances of each multicarrier technique are analyzed based on power spectral density and bit error rate. Simulation result shows that the power spectral density of FBMC with QAM using Hermite filter resulted in 4.7 dB reduction of out of band emission compared to FBMC with QAM using PHYDYAS filter. The bit error rate is also reduced for Vehicular A, Vehicular B, Pedestrian A, and Pedestrian B channel models.